All solid state battery

By integrating carbon materials and gaps within the electrode layers, the battery addresses cracking and peeling issues, enhancing cycle performance and reducing thickness in all-solid batteries.

JP7626709B2Active Publication Date: 2025-02-04TDK CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021554208
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-23
Filing Date
2020-09-29
Publication Date
2025-02-04
Estimated Expiration
2040-09-29

AI Technical Summary

Technical Problem

Existing all-solid batteries face issues with cracks and interface peeling due to internal stress, leading to increased internal resistance and decreased cycle characteristics, and existing solutions are complex to manufacture and increase battery thickness.

Method used

Incorporating multiple carbon materials with specific properties into the positive and negative electrode layers, along with strategically placed gaps and intermediate layers, to manage internal stress and prevent cracking and peeling.

Benefits of technology

The solution effectively suppresses cracks and peeling, improving the cycle characteristics and maintaining battery integrity while reducing thickness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626709000006
    Figure 0007626709000006
  • Figure 0007626709000007
    Figure 0007626709000007
  • Figure 0007626709000008
    Figure 0007626709000008
Patent Text Reader

Abstract

This all-solid-state battery comprises a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer. The positive electrode layer comprises a positive electrode current collector and a positive electrode active material layer contacting the positive electrode current collector. The negative electrode layer comprises a negative electrode current collector and a negative electrode active material layer contacting the negative electrode current collector. The positive electrode active material layer and / or the negative electrode active material layer comprises a plurality of voids and a plurality of carbon members in the interior thereof, with at least 8% of the plurality of voids being in contact with one of the plurality of carbon members.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an all-solid-state battery. This application claims priority based on Japanese Patent Application No. 2019-192584, filed on October 23, 2019, the contents of which are incorporated herein by reference. [Background technology]

[0002] In recent years, batteries have been used for various purposes. For example, batteries are used in portable batteries, and there is a demand for batteries to be small, lightweight, thin, and reliable. Batteries using electrolyte have problems such as electrolyte leakage and electrolyte depletion. Therefore, all-solid-state batteries using solid electrolytes have been attracting attention.

[0003] An all-solid-state battery has a positive electrode layer, a negative electrode layer, and a solid electrolyte layer. The positive electrode or the negative electrode expands and contracts when the all-solid-state battery is charged and discharged. The distortion caused by the expansion and contraction of the positive electrode or the negative electrode is one of the causes of cracks and is one of the causes of peeling at the lamination interface of each layer.

[0004] For example, Patent Document 1 discloses an all-solid-state battery having three solid electrolyte layers with different porosities between a positive electrode layer and a negative electrode layer. The three solid electrolyte layers with different porosities relieve internal stress and suppress the occurrence of cracks. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2013 / 175993 Summary of the Invention [Problem to be solved by the invention]

[0006] The cracks and interfacial peeling are one of the causes of an increase in internal resistance and a decrease in cycle characteristics.

[0007] Patent Document 1 describes a method for suppressing cracks. However, the structure is complicated and difficult to manufacture. In addition, the thickness in the stacking direction increases, which increases the thickness of the entire solid-state battery.

[0008] The present invention has been made in consideration of the above problems, and has an object to provide an all-solid-state battery capable of suppressing the occurrence of cracks and peeling at the laminate interface. [Means for solving the problem]

[0009] The inventors have found that by arranging a plurality of voids and a plurality of carbon materials in contact with each other in the negative electrode layer or the positive electrode layer, which are the cause of the generation of internal stress, it is possible to alleviate the internal stress generated in the all-solid-state battery and suppress the occurrence of cracks or interfacial peeling.

[0010] (1) An all-solid-state battery according to a first aspect includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, the positive electrode layer has a positive electrode current collector and a positive electrode active material layer in contact with the positive electrode current collector, the negative electrode layer has a negative electrode current collector and a negative electrode active material layer in contact with the negative electrode current collector, at least one of the positive electrode active material layer and the negative electrode active material layer has a plurality of voids and a plurality of carbon materials therein, and 8% or more of the plurality of voids are in contact with any of the plurality of carbon materials.

[0011] (2) In the all-solid-state battery according to the above aspect, at least a portion of the side margin layers arranged adjacent to and around the positive electrode layer and the negative electrode layer may have a plurality of voids therein.

[0012] (3) In the all-solid-state battery according to the above aspect, at least a portion of the side margin layers arranged adjacent to the outer periphery of the positive electrode layer and the negative electrode layer may have a plurality of voids and a carbon material therein, and 8% or more of the plurality of voids may be in contact with any of the plurality of carbon materials.

[0013] (4) In the all-solid-state battery according to the above aspect, each of the plurality of carbon materials may have shape anisotropy, and the major axis direction of each of the carbon materials may be oriented in an in-plane direction in which the positive electrode active material layer or the negative electrode active material layer extends.

[0014] (5) In the all-solid-state battery according to the above aspect, the plurality of carbon materials may have an average major axis length of 0.2 μm or more and 40 μm or less, and the plurality of carbon materials may have an average minor axis length of 0.4 μm or more and 5 μm or less.

[0015] (6) In the all-solid-state battery according to the above aspect, the proportion of the carbon materials in the layer including the carbon materials and the voids in the positive electrode active material layer and the negative electrode active material layer may be 2% or more and 40% or less.

[0016] (7) In the all-solid-state battery according to the above aspect, the proportion of the voids in the layer including the carbon materials and the voids in the positive electrode active material layer and the negative electrode active material layer may be 2% or more and 15% or less.

[0017] (8) In the all-solid-state battery according to the above aspect, in a cut surface intersecting the positive electrode layer and the negative electrode layer, 10% to 70% of the outer periphery of the cross section of the plurality of carbon materials may be in contact with any of the voids.

[0018] (9) The all-solid-state battery according to the above aspect may have an intermediate layer having ion conductivity between the solid electrolyte layer and at least one of the positive electrode layer and the negative electrode layer, and the intermediate layer may have a plurality of voids, and the proportion of the plurality of voids in the intermediate layer may be 0.1% or more and 8% or less. Effect of the Invention

[0019] The all-solid-state battery according to the above embodiment can suppress the occurrence of cracks and peeling at the laminate interface. [Brief description of the drawings]

[0020] [Figure 1]FIG. 1 is a schematic cross-sectional view of an all-solid-state battery according to an embodiment of the present invention. [Diagram 2] FIG. 2 is an enlarged view of a main part of the all-solid-state battery according to the present embodiment. [Diagram 3] FIG. 1 is a schematic plan view of an all-solid-state battery according to an embodiment of the present invention. [Figure 4] FIG. 1 is a schematic plan view of an all-solid-state battery according to an embodiment of the present invention. [Diagram 5] FIG. 4 is an enlarged view of a main part of an all-solid-state battery according to a first modified example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention will be described in detail below with reference to the drawings as appropriate. The drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the features of the present invention easier to understand, and the dimensional ratios of each component may differ from the actual ones. The materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not limited thereto, and may be appropriately modified and implemented within the scope of the present invention.

[0022] First, the directions are defined. The direction in which the positive electrode layer 1 and the negative electrode layer 2 described later are stacked is defined as the z direction. One of the in-plane directions in which the positive electrode layer 1 and the negative electrode layer 2 described later extend is defined as the x direction, and the direction perpendicular to the x direction is defined as the y direction.

[0023] [All-solid battery] FIG. 1 is a schematic cross-sectional view of an enlarged portion of an all-solid-state battery according to the first embodiment. As shown in FIG. 1, the all-solid-state battery 10 has a laminate 4. The laminate 4 has a plurality of positive electrode layers 1, a plurality of negative electrode layers 2, and a solid electrolyte layer 3 between the positive electrode layer 1 and the negative electrode layer 2. The positive electrode layer 1 is an example of a first electrode layer, and the negative electrode layer 2 is an example of a second electrode layer. One of the first electrode layer and the second electrode layer functions as a positive electrode, and the other functions as a negative electrode. The positive electrode layer 1 and the negative electrode layer 2 are connected to external terminals of corresponding polarities, respectively, and the positive electrode layer 1 and the negative electrode layer 2 are not in contact with each other.

[0024] The positive electrode layers 1 are each connected to a first external terminal 5, and the negative electrode layers 2 are each connected to a second external terminal 6. The first external terminal 5 and the second external terminal 6 are electrical contacts with the outside.

[0025] (Laminate) The laminate 4 has a plurality of positive electrode layers 1, a plurality of negative electrode layers 2, and a plurality of solid electrolyte layers 3. Each solid electrolyte layer 3 is disposed between the positive electrode layer 1 and the negative electrode layer 2. The all-solid-state battery 10 is charged and discharged by the exchange of lithium ions between the positive electrode layer 1 and the negative electrode layer 2 via the solid electrolyte layer 3.

[0026] "Positive and negative electrode layers" For example, there are a plurality of positive electrode layers 1 and a plurality of negative electrode layers 2 in the laminate 4. The positive electrode layers 1 and the negative electrode layers 2 are alternately laminated in the z direction with the solid electrolyte layer 3 sandwiched therebetween. Each positive electrode layer 1 and each negative electrode layer 2 extend in the xy plane. A first end of each positive electrode layer 1 is connected to the first external terminal 5, and a second end of each positive electrode layer 1 extends toward the second external terminal 6. A second end of each positive electrode layer 1 is not connected to the second external terminal 6. A first end of each negative electrode layer 2 is connected to the second external terminal 6, and a second end of each negative electrode layer 2 extends toward the first external terminal 5. A second end of each negative electrode layer 2 is not connected to the first external terminal 5. Between the positive electrode layer 1 and the second external terminal 6 and between the negative electrode layer 2 and the first external terminal 5, there is a material similar to that of the solid electrolyte layer 3. Of the end faces of the positive electrode layer 1 in the x direction, the end face closer to the second external terminal 6 is defined as a positive electrode end face S1, and of the end faces of the negative electrode layer 2 in the x direction, the end face closer to the first external terminal 5 is defined as a negative electrode end face S2. The positive electrode end faces S1 and S2 are, for example, surfaces perpendicular to the x direction.

[0027] The positive electrode layer 1 has a positive electrode current collector layer 1A and a positive electrode active material layer 1B. The negative electrode layer 2 has a negative electrode current collector layer 2A and a negative electrode active material layer 2B.

[0028] The positive electrode collector layer 1A and the negative electrode collector layer 2A extend in the xy plane. The positive electrode collector layer 1A and the negative electrode collector layer 2A contain a material having excellent electrical conductivity. The positive electrode collector layer 1A and the negative electrode collector layer 2A are portions containing 50% or more of a material having excellent electrical conductivity when the all-solid-state battery 10 is divided along the xy plane. Examples of the material having excellent electrical conductivity include silver, palladium, gold, platinum, aluminum, copper, and nickel. Copper does not easily react with the positive electrode active material, the negative electrode active material, and the solid electrolyte. For example, when copper is used for the positive electrode collector layer 1A and the negative electrode collector layer 2A, the internal resistance of the all-solid-state battery 10 can be reduced. The materials constituting the positive electrode collector layer 1A and the negative electrode collector layer 2A may be the same or different.

[0029] The positive electrode collector layer 1A may contain a positive electrode active material described later. The negative electrode collector layer 2A may contain a negative electrode active material described later. The content ratio of the active materials contained in each collector layer is not particularly limited as long as it functions as a collector. The volume ratio of the conductive material to the positive electrode active material in the positive electrode collector layer 1A is, for example, within a range of 90:10 to 70:30. Similarly, the volume ratio of the conductive material to the negative electrode active material in the negative electrode collector layer 2A is, for example, within a range of 90:10 to 70:30. When the positive electrode collector layer 1A and the negative electrode collector layer 2A contain a positive electrode active material and a negative electrode active material, respectively, the adhesion between the positive electrode collector layer 1A and the positive electrode active material layer 1B and the adhesion between the negative electrode collector layer 2A and the negative electrode active material layer 2B are improved.

[0030] The positive electrode active material layer 1B and the negative electrode active material layer 2B extend in the xy plane. The positive electrode active material layer 1B is formed on one or both sides of the positive electrode collector layer 1A. The positive electrode active material layer 1B may not be present on the surface of the positive electrode collector layer 1A on which the opposing negative electrode layer 2 is not present. The negative electrode active material layer 2B is formed on one or both sides of the negative electrode collector layer 2A. The negative electrode active material layer 2B may not be present on the surface of the negative electrode collector layer 2A on which the opposing positive electrode layer 1 is not present. For example, the positive electrode layer 1 or the negative electrode layer 2 located at the top or bottom of the laminate 4 may not have the positive electrode active material layer 1B or the negative electrode active material layer 2B on one side.

[0031] The positive electrode active material layer 1B and the negative electrode active material layer 2B contain active materials that exchange electrons during charge and discharge. The positive electrode active material layer 1B contains a positive electrode active material. The negative electrode active material layer 2B contains a negative electrode active material. The positive electrode active material layer 1B and the negative electrode active material layer 2B may each contain a conductive assistant, a binder, and the like. It is preferable that the positive electrode active material and the negative electrode active material can efficiently insert and extract lithium ions.

[0032] The positive electrode active material and the negative electrode active material are, for example, transition metal oxides and transition metal composite oxides. Specifically, the positive electrode active material and the negative electrode active material are, for example, lithium manganese composite oxide Li2Mn a Ma 1-a O3 (0.8 ≤ a ≤ 1, Ma = Co, Ni), lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese spinel (LiMn2O4), general formula: LiNi x Co y Mn z O2 (x + y + z = 1, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1), lithium vanadium compound (LiV2O5), olivine-type LiMbPO4 (where Mb is one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, Zr), lithium vanadium phosphate (Li3V2(PO4)3 or LiVOPO4), Li2MnO3-LiMcO2 (Mc = Mn, Co, Ni) represented by Li-excess solid solution positive electrode, lithium titanate (Li4Ti5O 12 )、Li s Ni t Co u Al v O2 (0.9 < s < 1.3, 0.9 < t + u + v < 1.1), and other composite metal oxides.

[0033] There is no clear distinction between the active materials constituting the positive electrode active material layer 1B or the negative electrode active material layer 2B. By comparing the potentials of two types of compounds, the compound showing a higher potential can be used as the positive electrode active material, and the compound showing a lower potential can be used as the negative electrode active material.

[0034] At least one of the positive electrode active material layer 1B and the negative electrode active material layer 2B has a plurality of voids and a plurality of carbon materials therein. Fig. 2 is a schematic diagram showing an enlarged view of the vicinity of the interface between the positive electrode layer 1 and the solid electrolyte layer 3 of the all-solid-state battery 10 according to this embodiment. The positive electrode active material layer 1B shown in Fig. 2 has a plurality of voids V and a plurality of carbon materials C. Although the positive electrode active material layer 1B is illustrated in Fig. 2, the negative electrode active material layer 2B may have a plurality of voids V and a plurality of carbon materials C, and the positive electrode active material layer 1B and the negative electrode active material layer 2B may have a plurality of voids V and a plurality of carbon materials C.

[0035] The plurality of carbon materials C are present between the active materials constituting the positive electrode active material layer 1B or the negative electrode active material layer 2B. The carbon materials C assist the conduction of electrons in the positive electrode active material layer 1B or the negative electrode active material layer 2B. The carbon materials C may be called conductive assistants. The carbon materials C are, for example, flake graphite, carbon nanotubes, carbon black, and graphene.

[0036] The ratio of the carbon materials C in the positive electrode active material layer 1B or the negative electrode active material layer 2B (hereinafter referred to as the area ratio of the carbon materials C) is, for example, preferably 2% to 40%, more preferably 3% to 30%. The area ratio of the carbon materials C is, for example, an average value of multiple cross-sectional images obtained by a scanning electron microscope (SEM).

[0037] First, five images each of the xz cross section and the yz cross section of the positive electrode active material layer 1B are taken. The area of ​​the positive electrode active material layer 1B is calculated from each image. In an actual SEM image, the interface between the positive electrode collector layer 1A and the positive electrode active material layer 1B and the interface between the positive electrode active material layer 1B and the solid electrolyte layer 3 are not flat. Therefore, the area of ​​the positive electrode active material layer 1B is converted to the area of ​​the region sandwiched between the xy plane extending at the average height position of the interface between the positive electrode collector layer 1A and the positive electrode active material layer 1B and the xy plane extending at the average height position of the interface between the positive electrode active material layer 1B and the solid electrolyte layer 3.

[0038] Next, the areas of the multiple carbon materials C in each image are obtained. The areas of the multiple carbon materials C can be obtained, for example, by the following procedure. First, the carbon material C is extracted from each of the captured images. The carbon material C can be distinguished because it looks different from other parts in the image. The area ratio of the multiple carbon materials C in the positive electrode active material layer 1B in each image is obtained, and the area ratio of the multiple carbon materials C is obtained by calculating the average value.

[0039] Each carbon material C has, for example, shape anisotropy. In FIG. 2, the carbon material C is illustrated as an ellipse in a schematic manner. However, the shape of the carbon material C does not matter. The shape of each carbon material C is, for example, amorphous. When the carbon material C is amorphous, the ellipse having the smallest area that contains the carbon material C is assumed to be the shape of the carbon material C, and the long axis length and the short axis length of the assumed ellipse are set to the long axis length and the short axis length of the carbon material C. Here, the ellipse to be assumed to be the shape of the carbon material C is determined as follows. Among the ellipses having the smallest area that contain the carbon material C, when the long axis length LLe of the ellipse is superimposed on the length LLc of the carbon material C in the longest direction (long axis direction) (LLe=LLc), the ellipse having the shortest short axis length SLe is assumed to be the shape of this carbon material C.

[0040] The aspect ratio of the carbon material C may be 2 or more and 29 or less, preferably 5 or more and 16 or less, and more preferably 8 or more and 13 or less. The aspect ratio is the value obtained by dividing the length in the major axis direction by the length in the minor axis direction.

[0041] The average long axis length of the carbon material C is, for example, 0.2 μm or more and 100 μm or less, and preferably more than 0.5 μm or more and 40 μm or less. The average short axis length of the carbon material C is, for example, 0.1 μm or more and 50 μm or less, preferably 0.2 μm or more and 20 μm or less, and more preferably 0.4 μm or more and 5 μm or less. When there are multiple carbon materials C, the average lengths in the long axis direction and the short axis direction of the carbon materials C are calculated by extracting two large carbon materials C from each of the above-mentioned 10 binary images, and averaging the average values ​​of a total of 20 carbon materials C.

[0042] Moreover, each carbon material C is preferably oriented in the xy plane. "Oriented in the xy plane" means that the long axis direction of the carbon material C is inclined at 45 degrees or more from the z direction. Moreover, it is preferable that the long axis direction of the carbon material C is approximately consistent with the in-plane direction in which the xy plane extends. "The long axis direction of the carbon material C is approximately consistent with the in-plane direction" means that the inclination angle of the long axis direction of the carbon material C with respect to the xy plane is 10 degrees or less. Here, it is not necessary that all the carbon materials C are oriented in the xy plane, or that the long axis direction of the carbon material C is approximately consistent with the in-plane direction. For example, it is preferable that 50% or more of the carbon materials C are oriented in the xy plane, or that the long axis direction of 50% or more of the carbon materials C is approximately consistent with the in-plane direction.

[0043] The multiple voids V are present inside the positive electrode active material layer 1B or the negative electrode active material layer 2B. Since the active material is responsible for the conduction of electrons during charging and discharging, it is common to densely pack the active material into the positive electrode active material layer 1B and the negative electrode active material layer 2B. The multiple voids V are intentionally provided.

[0044] The proportion of the multiple voids V in the positive electrode active material layer 1B or the negative electrode active material layer 2B (hereinafter referred to as porosity) is, for example, 2% to 15%, preferably 5% to 12%, and more preferably 8% to 12%. The porosity is calculated, for example, by dividing the difference between the theoretical mass and the actual measured mass by the actual measured mass. The theoretical mass is calculated by multiplying the average density of the positive electrode active material layer 1B or the negative electrode active material layer 2B by the volume. The actual measured mass is the mass that is actually measured.

[0045] Any of the voids V contacts the carbon material C. Each of the voids V is in the vicinity of the carbon material C. The ratio of the voids V in contact with the carbon material C is 8% or more, preferably 10% or more, and more preferably 30% or more. The ratio of the voids V in contact with the carbon material C is preferably 80% or less, more preferably 70% or less, and even more preferably 50% or less. For example, in a cut surface cut along the xz plane, it is preferable that 10% or more and 70% or less of the outer periphery of the cross section of the multiple carbon materials C contacts any of the voids V.

[0046] In order to arrange the voids V so as to be in contact with the carbon material C, it is preferable to make the carbon material C support a filler before the pasting step in producing the positive electrode active material layer 1B or the negative electrode active material layer 2B. Specifically, the filler can be supported on the carbon material C by dry mechanical particle composite formation using an impact compression shear type particle composite formation device, and the porosity in contact with the carbon material can be controlled by adjusting the amount of filler supported on the carbon material C.

[0047] "Solid electrolyte layer" The solid electrolyte layer 3 is located between each of the positive electrode layer 1 and the negative electrode layer 2. As will be described later, side margin layers 11, 12 made of the same material as the solid electrolyte layer 3 may be provided between the positive electrode layer 1 and the second external terminal 6 and between the negative electrode layer 2 and the first external terminal 5.

[0048] The solid electrolyte layer 3 includes a solid electrolyte. The solid electrolyte is a substance (e.g., particles) that can move ions by an externally applied electric field. For example, lithium ions move within the solid electrolyte by an externally applied electric field. The solid electrolyte is also an insulator that inhibits the movement of electrons.

[0049] The solid electrolyte contains, for example, lithium. The solid electrolyte may be, for example, any of oxide-based materials and sulfide-based materials. The solid electrolyte may be, for example, any of perovskite-type compounds, lysicone-type compounds, garnet-type compounds, nasicon-type compounds, thiolisicone-type compounds, glass compounds, and phosphate compounds. La 0.5 Li 0.5 TiO3 is an example of a perovskite compound. 14 Zn(GeO4)4 is an example of a lysicone-type compound. i7 La3Zr2O 12 is an example of a garnet-type compound. LiZr2(PO4)3, Li 1.3 Al 0.3 Ti 1.7 (PO4) 3、 Li 1.5 Al 0.5 Ge 1.5 (PO4)3, Li 1.55 Al0.2 Zr 1.7 S 0.25 P 9.75 O 12 , Li 1.4 Na 0.1 Zr 1.5 Al 0.5 (PO4)3, Li 1.4 Ca 0.25 Er 0.3 Zr 1.7 (PO4) 3.2 , Li 1.4 Ca 0.25 Yb 0.3 Zr 1.7 (PO4) 3.2 is an example of a Nasicon-type compound. 3.25 Ge 0.25 P 0.75 S 4、 Li3PS4 is an example of a thiolisicone-type compound. Li2S-P2S 5、 Li2O-V2O5-SiO2 is an example of a glass compound. Li3PO4, Li 3.5 S 0.5 P 0.5 O4, Li 2.9 PO 3.3 N 0.46 is an example of a phosphate compound. The solid electrolyte may contain one or more of these compounds.

[0050] The shape of the solid electrolyte is not particularly limited. The shape of the solid electrolyte may be, for example, spherical, ellipsoidal, needle-like, plate-like, scaly, tubular, wire-like, rod-like, or amorphous. The particle size of the solid electrolyte may be, for example, 0.1 μm or more and 10 μm or less, and may be 0.3 μm or more and 9 μm or less. The particle size of the particles is determined from the measured value (D50) obtained by particle size distribution measurement. D50 is the diameter of the particles at which the integrated value in the distribution curve obtained by particle size distribution measurement is 50%. The particle size distribution of the particles is measured, for example, by a particle size distribution measuring device using a laser diffraction / scattering method (microtrack method).

[0051] "Side margin layer" As shown in FIG. 1, the laminate 4 includes side margin layers 11 and 12 that are arranged on the outer periphery of the positive electrode layer 1 and the negative electrode layer 2 and contain a solid electrolyte. The side margin layers 11 and 12 are sometimes referred to as a positive electrode side margin layer and a negative electrode side margin layer, respectively. FIG. 3 is a cross-sectional view taken along the cutting line AA in FIG. 1. FIG. 4 is a cross-sectional view taken along the cutting line BB in FIG. 1. For convenience of explanation, the first external terminal 5 and the second external terminal 6 are also shown in FIG. 3 and FIG. 4. The side margin layer 11 has a first region R11a and a second region R11b. The first region R11a is a region of the side margin layer 11 that is closer to the second external terminal 6, and the second region R11b is a region of the side margin layer 11 that is closer to the first external terminal 5. The end face of the side margin layer 11 in the x direction on the second external terminal 6 side is the first end face S11, the minimum distance between the first end face S11 and the positive electrode layer 1 is L11a, and the length of the part that spans the side surface of the second external terminal 6 is L11b. The first region R11a is a region with a length L11a×2+L11b from the first end face S11. The second region R11b is a region that is at least the length L11a×2+L11b away from the first end face S11. Similarly, the side margin layer 12 has a first region R12a and a second region R12b. The first region R12a is a region of the side margin layer 12 that is closer to the first external terminal 5, and the second region R12b is a region of the side margin layer 12 that is closer to the second external terminal 6. If the end face of the side margin layer 12 in the x direction that is closer to the first external terminal 5 is the first end face S12, and the minimum distance between the second end face S12 and the negative electrode layer 2 is L12a, the first region R12a is a region with a length L12a×2+L12b from the first end face S12. The second region R12b is a region that is at least the length L12a×2+L12b away from the first end face S12.

[0052] The solid electrolyte contained in the side margin layers 11 and 12 may be the same as or different from the solid electrolyte contained in the solid electrolyte layer 3 .

[0053] The side margin layers 11 and 12 are preferably provided to eliminate the step between the solid electrolyte layer 3 and the positive electrode layer 1, and the step between the solid electrolyte layer 3 and the negative electrode layer 2. Therefore, the side margin layers 11 and 12 are formed in the main surface of the solid electrolyte layer 3 in an area other than the positive electrode layer 1 and the negative electrode layer 2, at substantially the same height as the positive electrode layer 1 or the negative electrode layer 2 (i.e., arranged next to the positive electrode layer 1 and the negative electrode layer 2, respectively). The presence of the side margin layers 11 and 12 eliminates the step between the solid electrolyte layer 3 and the positive electrode layer 1, and between the solid electrolyte layer 3 and the negative electrode layer 2, so that the density of the solid electrolyte 3 and each electrode layer is increased, and delamination and warping due to firing of the all-solid-state battery are less likely to occur.

[0054] At least some of the side margin layers 11, 12 may have a plurality of voids and a carbon material therein. When the side margin layers 11, 12 do not have a plurality of voids and a carbon material therein, the side margin layers 11, 12 may have the same configuration as the solid electrolyte layer 3. It is preferable that both of the side margin layers 11, 12 have a plurality of voids and a carbon material therein. The configuration of the plurality of voids and the carbon material contained in the side margin layers 11, 12 may be similar to the configuration of the plurality of voids V and the carbon material C contained in at least one of the positive electrode active material layer 1B and the negative electrode active material layer 2B.

[0055] Any of the multiple voids included in at least a part of the side margin layers 11 and 12 contacts the carbon material. Each void is in the vicinity of the carbon material. The ratio of the voids in contact with the carbon material is 8% or more, preferably 10% or more, and more preferably 30% or more. Here, when the side margin layers 11 and 12 have multiple voids and carbon material inside, it is preferable that the carbon material of the side margin layers 11 and 12 is present while avoiding the vicinity of the second external terminal 6 and the vicinity of the first external terminal 5, respectively. For example, it is preferable that the ratio of the carbon material in the first regions R11a and R12a is less than the ratio of the carbon material in the second regions R11b and R12b, respectively. Also, for example, the ratio of the carbon material in the first regions R11a and R12a is preferably 7% or less because self-discharge can be suppressed, and more preferably 5% or less. The ratio of the voids V in contact with the carbon material C is preferably 80% or less, more preferably 70% or less, and even more preferably 50% or less.

[0056] The ratio of the carbon materials in the second regions R11b and R12b of the side margin layers 11 and 12 (hereinafter referred to as the area ratio of the carbon materials in the side margin layers) is preferably, for example, 2% to 40%, and more preferably 3% to 30%. The area ratio of the carbon materials in the side margin layers is determined in the same manner as the ratio of the carbon materials C in the positive electrode active material layer 1B or the negative electrode active material layer 2B, using the average value of multiple cross-sectional images obtained by a scanning electron microscope (SEM).

[0057] The porosity of the side margin layers 11, 12 is preferably 3% or more. The porosity of the side margin layers 11, 12 is determined by the same method as that for the positive electrode active material layer 1B and the negative electrode active material layer 2B.

[0058] (Terminal) For example, a material having excellent electrical conductivity is used for the first external terminal 5 and the second external terminal 6. For example, the first external terminal 5 and the second external terminal 6 are any of silver, gold, platinum, aluminum, copper, tin, and nickel. The first external terminal 5 and the second external terminal 6 may be a single layer or multiple layers.

[0059] (protective layer) The all-solid-state battery 10 may have a protective layer on the outer periphery for electrically, physically, and chemically protecting the laminate 4 and the terminals. The protective layer is preferably made of a material that is excellent in insulation, durability, and moisture resistance and is environmentally safe. The protective layer is, for example, glass, ceramics, thermosetting resin, or photocurable resin. The protective layer may be made of one type of material or a combination of two or more types of materials. The protective layer may be a single layer or multiple layers. The protective layer is preferably an organic-inorganic hybrid made by mixing a thermosetting resin and ceramic powder.

[0060] Next, a method for producing the all-solid-state battery according to this embodiment will be described. The all-solid-state battery 10 may be produced by a co-firing method or a sequential firing method. The co-firing method is a method in which materials forming each layer are laminated and then sintered all at once. The sequential firing method is a method in which each layer is fired after being laminated. The co-firing method has a simpler process than the sequential firing method. In addition, the laminate 4 produced by the co-firing method is denser than the laminate 4 produced by the sequential firing method. Below, an example of using the co-firing method will be described.

[0061] First, pastes for each layer constituting the laminate 4 are prepared. The materials for the positive electrode collector layer 1A, the positive electrode active material layer 1B, the solid electrolyte layer 3, the side margin layers 11 and 12, the negative electrode active material layer 2B, and the negative electrode collector layer 2A are each made into a paste. The method of making the paste is not particularly limited. For example, the paste is obtained by mixing the powder of each material with a vehicle. The vehicle is a general term for a medium in a liquid phase. The vehicle includes a solvent and a binder.

[0062] A filler and a carbon material C are added to the cracks of at least one of the positive electrode active material layer 1B and the negative electrode active material layer 2B. When voids and a carbon material are included inside the side margin layers 11 and 12, the filler and the carbon material are also added to the cracks of the side margin layers 11 and 12. The filler is added by adhering to the carbon material C. The filler is, for example, a binder remover, a resin material, or a carbon material. All fillers volatilize during firing. The carbon material used as the filler volatilizes during firing and can be distinguished from the carbon material C. The filler is, for example, a pore-forming material. The pore-forming material is, for example, resin particles such as polyethylene, polypropylene, and polyethylene terephthalate. The filler attached to the carbon material C volatilizes during firing to form voids V.

[0063] Next, a green sheet is prepared. The green sheet is obtained by processing the paste into a sheet shape. For example, the paste is applied to a substrate such as PET (polyethylene terephthalate) in a desired order, dried as necessary, and then peeled off from the substrate to obtain the green sheet. The method of applying the paste is not particularly limited. For example, known methods such as screen printing, application, transfer, doctor blade, etc. can be adopted.

[0064] When preparing the green sheets for the positive electrode active material layer 1B and the negative electrode active material layer 2B, the carbon material C is oriented in the in-plane direction by controlling the coating speed or coating through a mesh having openings.

[0065] The green sheets thus produced are stacked in a desired order and number of layers. Alignment, cutting, etc. are performed as necessary to produce a laminate. When producing a parallel or series-parallel battery, the positive and negative current collector layers are aligned so that the end faces of the positive and negative current collector layers do not coincide with each other.

[0066] The laminate may be produced after preparing the positive electrode active material layer unit and the negative electrode active material layer unit described below.

[0067] First, the paste for the solid electrolyte layer is formed into a sheet shape on a PET film by a doctor blade method and dried. Next, the paste for the positive electrode active material layer is printed on the green sheet for the solid electrolyte layer by screen printing and dried.

[0068] Next, the paste for the positive electrode collector layer is printed by screen printing on the dried paste for the positive electrode active material layer and dried. The paste for the positive electrode collector layer is again printed by screen printing on the dried paste for the positive electrode active material layer and dried. Then, the paste for the side margin layer is screen printed on the area of ​​the solid electrolyte layer sheet other than the positive electrode layer and dried to form a side margin layer having approximately the same height as the positive electrode layer. The PET film is then peeled off to produce a positive electrode unit. The positive electrode unit includes a positive electrode layer 1 formed by laminating a positive electrode active material layer 1B / a positive electrode current collector layer 1A / a positive electrode active material layer 1B in this order on the main surface of a solid electrolyte layer 3, and a side margin layer 11.

[0069] The negative electrode unit is also produced by the same procedure. The negative electrode unit has a negative electrode layer 2, which is formed by laminating a negative electrode active material layer 2B / a negative electrode current collector layer 2A / a negative electrode active material layer 2B in this order on the main surface of a solid electrolyte layer 3, and a side margin layer 12.

[0070] Next, the positive electrode unit and the negative electrode unit are stacked. The positive electrode unit and the negative electrode unit are stacked so that the solid electrolyte layers of the respective units do not face each other. The stacked laminate is stacked in the order of positive electrode active material layer 1B / positive electrode current collector layer 1A / positive electrode active material layer 1B / solid electrolyte layer 3 / negative electrode active material layer 2B / negative electrode current collector layer 2A / negative electrode active material layer 2B / solid electrolyte layer 3. The positive electrode unit and the negative electrode unit are stacked with a shift so that the positive electrode current collector layer 1A is exposed on a first end face of the laminate and the negative electrode current collector layer 2A is exposed on a second end face opposite to the first end face. For example, a solid electrolyte layer sheet of a predetermined thickness is further stacked on the top layer and the bottom layer in the stacking direction and dried.

[0071] Next, the produced laminate is pressure-bonded together. The pressure-bonding is performed while heating. The heating temperature is, for example, 40 to 95°C. Next, the pressure-bonded laminate is sintered. For example, the sintering is performed by heating in a temperature range of 500°C to 1100°C in a nitrogen atmosphere. The sintering time is, for example, 0.1 to 3 hours. The laminate 4 is obtained by sintering. At this time, the filler becomes voids V.

[0072] The sintered body may be placed in a cylindrical container together with an abrasive such as alumina and barrel-polished. The corners of the sintered body are chamfered by polishing. Polishing may also be performed by sandblasting or the like.

[0073] Finally, a first external terminal 5 and a second external terminal 6 are attached to the laminate 4. The first external terminal 5 is formed so as to be electrically connected to each of the positive electrode current collector layers 1A. The second external terminal 6 is formed so as to be electrically connected to each of the negative electrode current collector layers 2A. For example, the first external terminal 5 is connected to the positive electrode current collector layer 1A exposed from the side surface of the laminate 4, and the second external terminal 6 is connected to the negative electrode current collector layer 2A exposed from the side surface of the laminate 4. The first external terminal 5 and the second external terminal 6 can be produced by, for example, a sputtering method, a dipping method, a spray coating method, or the like.

[0074] In the all-solid-state battery according to this embodiment, at least one of the positive electrode active material layer 1B and the negative electrode active material layer 2B has a plurality of carbon materials C and a plurality of voids V, and at least a part of the plurality of voids V is in contact with any of the carbon materials C, thereby making it possible to suppress the occurrence of cracks and peeling at the lamination interface. When the occurrence of cracks and peeling at the lamination interface is suppressed, the cycle characteristics of the all-solid-state battery are improved.

[0075] The positive electrode active material layer 1B and the negative electrode active material layer 2B are densely formed to enhance the electron conductivity. For this reason, it is common to minimize voids in the positive electrode active material layer 1B and the negative electrode active material layer 2B. However, as a result of the study in the examples described later, it was found that the cycle characteristics are improved by providing the voids V in contact with the carbon material C.

[0076] It is not clear why the cycle characteristics improve when the voids V are in contact with the carbon material C. The stress caused by the expansion and contraction of the active material during charging and discharging can be more easily alleviated than when the voids V exist alone. When stress is applied, the order of most likely to become distorted is voids V, carbon material C, and active material. In other words, it may be because the voids V are formed along the carbon material C, so that the stress is propagated in the order of active material, carbon material C, and voids V, and the stress is alleviated in stages.

[0077] Furthermore, when the carbon material C has shape anisotropy, the carbon material C easily collapses in the minor axis direction, and the volume change of the active material can be appropriately buffered. The positive electrode active material layer 1B and the negative electrode active material layer 2B mainly expand and contract in the z direction. When the carbon material C is oriented in the xy plane, the minor axis direction of the carbon material C becomes the z direction. The carbon material C easily collapses in the minor axis direction, and by having the minor axis direction of the carbon material C become the z direction, cracks and interfacial peeling can be more effectively suppressed.

[0078] The above describes the embodiments of the present invention in detail with reference to the drawings. However, each configuration and combination thereof in each embodiment is merely an example, and addition, omission, substitution, and other modifications of the configuration are possible without departing from the spirit of the present invention.

[0079] (First Modification) Fig. 3 is an enlarged cross-sectional view of a main part of the all-solid-state battery according to the first modified example. Fig. 3 is an enlarged view of the vicinity of the interface between the cathode layer 1 and the solid electrolyte layer 3 of the all-solid-state battery. The all-solid-state battery shown in Fig. 3 differs from the all-solid-state battery shown in Fig. 2 in that it has an intermediate layer 7 between the cathode layer 1 and the solid electrolyte layer 3. Although Fig. 3 shows an example in which the intermediate layer 7 is between the cathode layer 1 and the solid electrolyte layer 3, the intermediate layer 7 may be between the anode layer 2 and the solid electrolyte layer 3.

[0080] The intermediate layer 7 extends in the xy plane and is located between the positive electrode active material layer 1B or the negative electrode active material layer 2B and the solid electrolyte layer 3. The intermediate layer 7 is a layer having a composition between the active material constituting the positive electrode active material layer 1B or the negative electrode active material layer 2B and the solid electrolyte constituting the solid electrolyte layer 3. For example, when the positive electrode active material layer 1B or the negative electrode active material layer 2B is lithium vanadium phosphate (Li3V2(PO4)3, Li2VTi(PO4)3, LiVOPO4) and the solid electrolyte is lithium zirconium phosphate (LiZr2(PO4)3), the intermediate layer 7 is lithium zirconium phosphate containing vanadium or lithium vanadium phosphate containing zirconium. The lithium zirconium phosphate containing vanadium is lithium zirconium phosphate in which part of the zirconium in lithium vanadium phosphate is replaced with vanadium. The lithium vanadium phosphate containing zirconium is lithium vanadium phosphate in which part of the vanadium in lithium vanadium phosphate is replaced with zirconium. The intermediate layer 7 increases the bonding strength between the positive electrode active material layer 1B or the negative electrode active material layer 2B and the solid electrolyte layer 3.

[0081] The intermediate layer 7 may have, for example, a plurality of voids V2. The proportion of the plurality of voids V2 in the intermediate layer 7 is preferably 0.1% or more and 8% or less. When the intermediate layer 7 also has a plurality of voids V2, the internal stress caused by the expansion and contraction of the active material can be alleviated, and the occurrence of cracks and interfacial peeling can be more effectively suppressed. Furthermore, when the proportion of the plurality of voids V2 in the intermediate layer 7 is not too high, the bonding strength between the positive electrode active material layer 1B or the negative electrode active material layer 2B and the solid electrolyte layer 3 can be maintained, and the occurrence of interfacial peeling can be more effectively suppressed.

[0082] The intermediate layer 7 is obtained by separately preparing a layer whose constituent elements have been adjusted in advance, and inserting the layer between the solid electrolyte layer 3 and the positive electrode active material layer 1B or the negative electrode active material layer 2B. The sintering conditions may be adjusted to thermally diffuse the constituent element of the solid electrolyte layer 3 (e.g., zirconium) into the positive electrode active material layer 1B or the negative electrode active material layer 2B, or to thermally diffuse the constituent element of the positive electrode active material layer 1B or the negative electrode active material layer 2B (e.g., vanadium) into the solid electrolyte layer 3.

[0083] The all-solid-state battery according to the first modification has the same effects as the all-solid-state battery according to the first embodiment. In addition, the intermediate layer 7 increases the bonding strength between the positive electrode active material layer 1B or the negative electrode active material layer 2B and the solid electrolyte layer 3, and can more effectively suppress the occurrence of interfacial peeling. EXAMPLES

[0084] Example 1 The all-solid-state battery of Example 1 was fabricated as follows.

[0085] (Preparation of active material) The active material used was lithium vanadium phosphate, which was prepared by the following method. Starting materials were Li2CO3, V2O5, and NH4H2PO4, which were wet mixed in a ball mill for 16 hours. The powder obtained after dehydration and drying was calcined in a nitrogen-hydrogen mixed gas at 850°C for 2 hours. The calcined product was wet-pulverized in a ball mill, and then dehydrated and dried to obtain the active material. An X-ray diffraction device was used to confirm that the powder produced had the same crystal structure as Li3V2(PO4)3.

[0086] (Preparation of Paste for Active Material Layer) The paste for the active material layer was prepared by adding 95.4 parts of the obtained active material powder, 0.6 parts of filler, and 4 parts of flat carbon powder, 15 parts of ethyl cellulose as a binder, and 65 parts of dihydroterpineol as a solvent, and mixing and dispersing them to prepare a paste for the positive electrode active material layer and a paste for the negative electrode active material layer. The filler was polypropylene. The carbon material was scaly graphite. The carbon material had a long axis length of 0.5 μm, a short axis length of 0.1 μm, and an aspect ratio of 5.0. The filler was supported on the carbon material using an impact compression shear type particle composite device.

[0087] (Preparation of solid electrolyte) As a solid electrolyte, the LZP-based Nasicon-type compound (e.g. LiZr 1.7 Ca 0.3(PO4)3) was used. Li2CO3, ZrO2, CaCO3, and NH4H2PO4 were used as starting materials, and were wet mixed in a ball mill for 16 hours, then dehydrated and dried, and the resulting powder was calcined in air at 900°C for 2 hours. After calcination, the powder was wet ground in a ball mill for 16 hours, and then dehydrated and dried to obtain a solid electrolyte powder. It was confirmed using an X-ray diffraction device (XRD) that the crystal structure of the powder produced was the same as that of the LZP-based Nasicon-type compound.

[0088] (Preparation of paste for solid electrolyte layer) The solid electrolyte layer paste was prepared by adding 100 parts of solid electrolyte powder, 100 parts of ethanol and 200 parts of toluene as solvents, and wet mixing them in a ball mill. Then, 16 parts of a polyvinyl butyral binder and 4.8 parts of benzyl butyl phthalate were further added and mixed to prepare the solid electrolyte layer paste.

[0089] (Preparation of sheets for solid electrolyte layer) The paste for the solid electrolyte layer was formed into a sheet using a doctor blade method with a PET film as a substrate to obtain a sheet for the solid electrolyte layer having a thickness of 15 μm.

[0090] (Preparation of paste for current collector layer) To prepare a positive electrode current collector and a negative electrode current collector, Cu and the active material lithium vanadium titanium phosphate were mixed in a volume ratio of 80 / 20, and then 100 parts of the obtained mixture was mixed and dispersed with 10 parts of ethyl cellulose as a binder and 50 parts of dihydroterpineol as a solvent to prepare a current collector layer paste.

[0091] (Preparation of intermediate layer substrate) The intermediate layer substrate was prepared by wet mixing the lithium vanadium phosphate powder prepared as the active material with the LZP-based Nasicon-type compound powder prepared as the solid electrolyte in a ball mill for 16 hours, dehydrating and drying the resulting powder, which was then calcined in a nitrogen-hydrogen mixed gas at 850°C for 2 hours. The calcined product was wet-pulverized in a ball mill, and then dehydrating and drying to obtain the intermediate layer substrate powder.

[0092] (Preparation of intermediate layer paste) The intermediate layer paste was prepared by adding 0.5 parts of filler (polyethylene), 15 parts of ethyl cellulose as a binder, and 65 parts of dihydroterpineol as a solvent to 100 parts of the intermediate layer base powder, and mixing and dispersing them.

[0093] (Preparation of external terminal paste) Silver powder, epoxy resin, and a solvent were mixed and dispersed to prepare a thermosetting external electrode paste.

[0094] Using these pastes, an all-solid-state battery of Example 1 was fabricated as follows.

[0095] (Fabrication of Positive Electrode Layer Unit) First, a 0.2 μm thick intermediate layer (referred to as the first positive electrode intermediate layer) was formed on the solid electrolyte layer sheet by screen printing, and dried at 80° C. for 10 minutes. Next, a 5 μm thick positive electrode active material layer (referred to as the first positive electrode active material layer) was formed on the solid electrolyte layer sheet by screen printing, and dried at 80° C. for 10 minutes. A 5 μm thick positive electrode current collector layer was further formed on the solid electrolyte layer sheet by screen printing, and dried at 80° C. for 10 minutes. A 0.2 μm thick intermediate layer (referred to as the second positive electrode active material layer) was further formed on the solid electrolyte layer sheet by screen printing, and dried at 80° C. for 10 minutes. Next, a side margin layer having a height approximately the same as that of the positive electrode layer was formed on the outer periphery of one end of the positive electrode layer by screen printing, and dried at 80° C. for 10 minutes. Next, the PET film was peeled off to obtain a sheet of the positive electrode layer unit.

[0096] (Fabrication of negative electrode layer unit) Next, a 0.2 μm thick intermediate layer (referred to as the first negative electrode intermediate layer) was formed on the solid electrolyte layer sheet by screen printing, and dried at 80° C. for 10 minutes. Next, a 5 μm thick negative electrode active material layer (referred to as the first negative electrode active material layer) was formed thereon, and dried at 80° C. for 10 minutes. A 5 μm thick negative electrode current collector layer was further formed thereon by screen printing, and dried at 80° C. for 10 minutes. A 5 μm thick negative electrode active material layer (referred to as the second negative electrode active material layer) was further formed thereon by screen printing, and dried at 80° C. for 10 minutes. A 0.2 μm thick intermediate layer (referred to as the second negative electrode intermediate layer) was further formed thereon by screen printing, and dried at 80° C. for 10 minutes, thereby preparing a negative electrode layer on the solid electrolyte layer sheet. Next, a margin layer having a height approximately the same as that of the negative electrode layer was formed on the outer periphery of one end of the negative electrode layer by screen printing, and dried at 80° C. for 10 minutes. Next, the PET film was peeled off to obtain a sheet of the negative electrode layer unit.

[0097] (Preparation of Laminate) A laminated substrate was produced by laminating multiple positive electrode layer units and negative electrode layer units alternately while offsetting one end of each unit so that they did not coincide. Furthermore, multiple solid electrolyte sheets were laminated as outer layers on both main surfaces of the laminated substrate to provide 200 μm outer layers. This was thermocompressed by a die press, and then cut to produce an unfired all-solid-state battery laminate. Next, the laminate was de-bindered and fired to obtain an all-solid-state battery laminate. The laminate was fired in nitrogen at a heating rate of 200 ° C / hour up to a firing temperature of 1000 ° C, held at that temperature for 2 hours, and naturally cooled before being removed. The filler became voids, and some of the voids were in contact with the carbon material.

[0098] (External electrode formation process) An external terminal paste was applied to the end faces of the laminate of the all-solid-state battery and thermally cured at 150°C for 30 minutes to form a pair of external electrodes.

[0099] The dimensions of the fabricated all-solid-state battery were approximately 4.5 mm x 3.2 mm x 1.1 mm.

[0100] The initial capacity and cycle characteristics of the prepared all-solid-state battery were obtained. The initial capacity and cycle characteristics were measured using a secondary battery charge / discharge tester. The voltage range was from 0.2V to 2.6V. First, as a pre-treatment, only the initial charge was performed at a constant current of 0.2C. Then, charge / discharge was performed to obtain cycle characteristics. Charging was performed at a constant current and constant voltage. Charging was performed at a current value of 0.2C, and after reaching 2.6V, it was terminated when the current value became 5% of the 0.2C current value. Discharging was performed under the condition of discharging at a current value of 0.1C. The cycle characteristics were evaluated as a capacity retention rate (%). The capacity retention rate (%) is the ratio of the discharge capacity after 100 cycles to the initial discharge capacity, with the discharge capacity at the first cycle being the initial discharge capacity. The capacity retention rate (%) is expressed by the following formula. Capacity retention rate (%) = ("Discharge capacity after 100 cycles" / "Discharge capacity at the first cycle") x 100

[0101] In addition, an all-solid-state battery produced under similar conditions was cut, and the area ratio of the carbon material in the positive electrode active material layer and the negative electrode active material layer, the porosity, and the like were determined.

[0102] (Examples 2 to 6) The difference from Example 1 is that the long axis length and the short axis length of the carbon material were changed under the condition that the aspect ratio was approximately constant. The long axis length, the short axis length and the aspect ratio of the carbon material were adjusted by the shape of the carbon material added to the green sheets of the positive electrode active material layer and the negative electrode active material layer. In Examples 2 to 6, the same measurements as in Example 1 were performed.

[0103] (Examples 7 to 12) The difference from Example 1 is that the long axis length and the short axis length of the carbon material were changed. The long axis length, the short axis length and the aspect ratio of the carbon material were adjusted by the shape of the carbon material added to the paste of the positive electrode active material layer and the negative electrode active material layer. In Examples 7 to 12, the same measurements as in Example 1 were performed.

[0104] (Examples 13 to 18) The difference from Example 1 is that the minor axis length of the carbon material was fixed, and the major axis length and aspect ratio of the carbon material were changed. The major axis length and aspect ratio of the carbon material were adjusted by the shape of the carbon material added to the paste of the positive electrode active material layer and the negative electrode active material layer. In Examples 13 to 18, the same measurements as in Example 1 were performed.

[0105] (Examples 19 to 24) The difference from Example 1 is that a carbon material having a long axis length of 5.1 μm and a short axis length of 0.9 μm was used, and the ratio of the carbon material occupying the positive electrode active material layer and the negative electrode active material layer and the porosity were changed. The ratio of the carbon material occupying the positive electrode active material layer and the negative electrode active material layer was adjusted by the amount of the carbon material added to the paste of the positive electrode active material layer and the negative electrode active material layer. The porosity was adjusted by the amount of the filler added to the paste of the positive electrode active material layer and the negative electrode active material layer. In Examples 19 to 24, the same measurements as in Example 1 were performed.

[0106] (Examples 25 to 30) The difference from Example 1 is that the ratio of the voids in contact with the carbon material among the multiple voids was changed. The ratio of the voids in contact with the carbon material was adjusted by adjusting the amount of filler supported by the carbon material using an impact compression shear type particle composite device. In Examples 25 to 30, the same measurements as in Example 1 were performed.

[0107] (Example 31) A carbon material having a major axis length of 10.0 μm and a minor axis length of 0.9 μm was used, and a mesh was not used when preparing the paste for the positive electrode active material layer and the negative electrode active material layer. The other conditions were the same as those in Example 1. The carbon material in Example 31 was not oriented in a particular direction, and the direction of the major axis was random. In Example 31, the same measurements as in Example 1 were performed.

[0108] (Examples 32 to 36) A carbon material having a major axis length of 10.0 μm and a minor axis length of 0.9 μm was used, and the porosity of the positive electrode active material layer and the negative electrode active material layer was changed. The porosity was adjusted by the amount of filler added. The other conditions were the same as in Example 1. In Examples 32 to 36, the same measurements as in Example 1 were performed.

[0109] (Example 37) This example differs from Example 21 in that the amount of filler added to the intermediate layer was changed to change the porosity of the intermediate layer. The other conditions were the same as in Example 21.

[0110] Comparative Example 1 This example differs from Example 1 in that a carbon material having a major axis length of 10.0 μm and a minor axis length of 0.9 μm was used, and the ratio of voids in contact with the carbon material was 2%. The other conditions were the same as those of Example 1.

[0111] (Example 12-2) In Example 12-2, a side margin layer was printed using a paste for a side margin layer (with voids), and an all-solid-state battery having multiple voids and multiple carbon materials in the entire side margin layer was fabricated. The other conditions were the same as those of Example 12.

[0112] (Preparation of paste for side margin layer (with gap)) The paste for the side margin layer (with voids) was prepared by adding 98.6 parts of solid electrolyte powder, 0.4 parts of filler, and 1 part of flat carbon powder, 15 parts of ethyl cellulose as a binder, and 65 parts of dihydroterpineol as a solvent, and mixing and dispersing them. The filler was polypropylene. The carbon material was scaly graphite. The carbon material had a long axis length of 0.2 μm, a short axis length of 0.1 μm, and an aspect ratio of 2.0. The filler was supported on the carbon material using an impact compression shear type particle composite device.

[0113] (Examples 12-3 to 12-6) In Examples 12-3 to 12-6, the amount of filler was adjusted so that the porosity of the side margin layer was different. Other conditions were the same as in Example 12-2. In Example 12, the porosity of the side margin layer was less than 2%. In Table 3, the porosity of the side margin layer was added to Example 12 in Table 1, and it was expressed as Example 12-1. In Examples 12-2 to 12-6, the same measurements as in Example 1 were performed, and the porosity of the side margin layer was also measured.

[0114] (Examples 101 to 136) As Examples 101 to 136, all-solid-state batteries were produced except for the step of forming the intermediate layer. That is, the all-solid-state batteries of Examples 101 to 136 did not have an intermediate layer. Other conditions for Examples 101 to 136 were the same as those for Examples 1 to 36, respectively.

[0115] Comparative Example 2 As Comparative Example 2, an all-solid-state battery was produced without the step of forming the intermediate layer. That is, the all-solid-state battery of Comparative Example 2 does not have an intermediate layer. The other conditions of Comparative Example 2 were the same as those of Comparative Example 1.

[0116] The above results are summarized in Tables 1 to 5. The initial capacity in Tables 1 to 5 is a ratio when the initial capacity of Example 1 is taken as 100%. Tables 4 and 5 show the results of Examples 101 to 136 and Comparative Example 2. The all-solid-state batteries of Examples 101 to 136 and Comparative Example 2 do not have an intermediate layer. Therefore, the area ratio of voids in the intermediate layer was not measured in the all-solid-state batteries of Examples 101 to 136 and Comparative Example 2.

[0117] [Table 1]

[0118] [Table 2]

[0119] [Table 3]

[0120] [Table 4]

[0121] [Table 5] [Explanation of symbols]

[0122] 1...Positive electrode layer, 1A...Positive electrode current collector layer, 1B...Positive electrode active material layer, 2...Negative electrode layer, 2A...Negative electrode current collector layer, 2B...Negative electrode active material layer, 3...Solid electrolyte layer, 4...Laminated body, 5...First external terminal, 6...Second external terminal, C...Carbon material, V, V2...Void

Claims

1. a laminate including a positive electrode layer, a negative electrode layer, a solid electrolyte layer between the positive electrode layer and the negative electrode layer, and side margin layers arranged adjacent to and around the positive electrode layer and the negative electrode layer, the positive electrode layer has a positive electrode current collector and a positive electrode active material layer in contact with the positive electrode current collector, the negative electrode layer has a negative electrode current collector and a negative electrode active material layer in contact with the negative electrode current collector, At least one of the positive electrode active material layer and the negative electrode active material layer has a plurality of voids and a plurality of carbon materials therein, At least a portion of the side margin layer has a plurality of voids and a carbon material therein, an all-solid-state battery, wherein 8% or more of a cross-sectional outer periphery of the plurality of voids in a layer including the plurality of carbon materials and the plurality of voids, of the positive electrode active material layer and the negative electrode active material layer, is in contact with any of the plurality of carbon materials in the layer including the plurality of carbon materials and the plurality of voids, of the positive electrode active material layer and the negative electrode active material layer, and 8% or more of the plurality of voids in the side margin layer is in contact with any of the plurality of carbon materials in the side margin layer.

2. The plurality of carbon materials provided in the laminate each have shape anisotropy, 2. The all-solid-state battery according to claim 1, wherein the major axis direction of each carbon material is oriented in an in-plane direction in which the positive electrode active material layer or the negative electrode active material layer extends.

3. The average major axis length of the plurality of carbon materials provided in the laminate is 0.2 μm or more and 40 μm or less, 3. The all-solid-state battery according to claim 1, wherein an average minor axis length of the plurality of carbon materials provided in the laminate is 0.4 μm or more and 5 μm or less.

4. 4. The all-solid-state battery according to claim 1, wherein a ratio of the plurality of carbon materials in the layer including the plurality of carbon materials and the plurality of voids in the positive electrode active material layer and the negative electrode active material layer is 2% or more and 40% or less.

5. 5. The all-solid-state battery according to claim 1, wherein a ratio of the plurality of voids in a layer including the plurality of carbon materials and the plurality of voids in the positive electrode active material layer and the negative electrode active material layer is 2% or more and 15% or less.

6. At a cut surface intersecting the positive electrode layer and the negative electrode layer, The all-solid-state battery according to any one of claims 1 to 5, wherein 10% to 70% of the cross-sectional outer periphery of the plurality of carbon materials provided in the laminate is in contact with any void.

7. The laminate has an intermediate layer having ion conductivity between at least one of the positive electrode layer and the negative electrode layer and the solid electrolyte layer, The intermediate layer has a plurality of voids, The all-solid-state battery according to any one of claims 1 to 6, wherein the proportion of the plurality of voids in the intermediate layer is 0.1% or more and 8% or less.

Citation Information

Patent Citations

  • Secondary battery, and method for manufacturing the same

    JP2012186135A

  • Electrode and all-solid state nonaqueous electrolyte battery

    JP2012243645A

  • All-solid type secondary battery

    JP2014192041A

  • Method of manufacturing highly multilayered all solid lithium ion secondary battery

    JP2016207540A

  • Negative electrode for all-solid battery

    JP2017054720A